RESILIENSI SINGLE PARENT - Sumarni, Neni (Journal of Education Counseling, 2024)
The dream of a married couple always wants to be together until they die. Unfortunately, achieving that dream is not as easy as one would like, there are divorced couples living and dead. There are those who are strong in going through the problem, there are also running away from the problem. Bearing the burden of educating, raising, nurturing and providing living expenses until a child is successful is not easy. People who can survive in difficult conditions are great people. The purpose of this study was to determine the factors that cause single parents to survive in difficult conditions. This research method chose a qualitative, phenomenological approach. The informant selection method used purposive sampling. Data collection techniques using unstructured observation, unstructured interviews and documentation. Data analysis uses the Miles and Huberman models, namely data collection, data reduction and data presentation. The validity of the data uses a credibility test by increasing persistence and reading articles. The results of the study show that single parents are able to survive in difficult circumstances and can develop because the child has the right mindset and has an environment that is always supportive. the conclusion is no matter how difficult life can still survive because there is something to fight for. Impian sepasang suami istri selalu ingin bersama sampai meninggal dunia. Sayang, untuk meraih impian itu tidak semudah yang diinginkan ada pasangan cerai mati dan hidup. Ada yang kuat menjalani masalah tersebut, ada juga lari dari masalah. Menanggung beban mendidik, membesarkan, mengayomi dan memberikan biaya hidup sampai anak sukses tidak mudah. Orang yang mampu bertahan di dalam kondisi sulit adalah orang hebat. Tujuan penelitian ini adalah untuk mengetahui faktor-faktor yang menyebabkan single parent bisa bertahan di dalam kondisi sulit. Metode penelitian ini memilih kualititatif, pendekatan fenomenologi. Metode pemilihan informan menggunakan purposive sampling. Teknik pengumpulan data menggunakan observasi tak berstruktur, wawancara tak berstruktur dan dokumentasi. Analisis data menggunakan model Miles dan Huberman yaitu pengumpulan data, reduksi data dan penyajian data. Keabsahan data menggunakan uji kredibilitas dengan meningkatkan ketekunan dan membaca artikel. Hasil penelitian, single parent mampu bertahan dalam keadaan sulit dan bisa berkembang disebabkan karena anak, mindset benar dan memiliki lingkungan yang selalu mendukung. kesimpulannya sesulit apa pun hidup tetap bisa bertahan karena ada yang diperjuangkan